A new species of Lampanyctus (Myctophiformes: Myctophidae) from the western South Pacific Ocean - Clements, Kendall D.; Stewart, Andrew L. (Zootaxa, 2026)
Lampanyctus mendeleevi sp. nov. is described from the New Zealand-east Australian region of the western South Pacific Ocean. It has relatively long pectoral fins, no cheek photophores, no luminous tissue at the base of the adipose fin, and an infracaudal gland extending the entire length of the caudal peduncle expanded to touch or nearly touch the AOp series.